2013
DOI: 10.1108/pijpsm-01-2013-0005
|View full text |Cite
|
Sign up to set email alerts
|

Diversity in municipal police agencies: a national examination of minority hiring and promotion

Abstract: Purpose – The purpose of this paper is to better understand the institutional and external factors associated with African-American and Latino representation in policing at the line and managerial ranks. Line representation analyses utilize new data sources and a full range of theoretically informed covariates. Managerial representation analyses provide the first comprehensive attempt to understand the dynamics behind minority promotion. Design/methodology/approach – Portions of the 2000 US Census of Popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(54 citation statements)
references
References 48 publications
1
52
1
Order By: Relevance
“…Specifically, studies on policing and ethnic and gender integration have found that the employment and promotion of minority men and women officers is related inversely with police ranks (e.g., Guajardo, 2014aGuajardo, & 2015bGustafson, 2013;Harrington & Lonsway, 2004;Martin, 2004;Schulz, 2004;Townsey, 1982). Gustafson (2013) observes that opportunities for advancement in policing are rare. In examining minority diversity in managerial police positions, Gustafson (2013) found that the promotion of minorities to higher positions is independent of the percentage of minorities in subordinate positions.…”
Section: Hierarchical Structurementioning
confidence: 96%
See 3 more Smart Citations
“…Specifically, studies on policing and ethnic and gender integration have found that the employment and promotion of minority men and women officers is related inversely with police ranks (e.g., Guajardo, 2014aGuajardo, & 2015bGustafson, 2013;Harrington & Lonsway, 2004;Martin, 2004;Schulz, 2004;Townsey, 1982). Gustafson (2013) observes that opportunities for advancement in policing are rare. In examining minority diversity in managerial police positions, Gustafson (2013) found that the promotion of minorities to higher positions is independent of the percentage of minorities in subordinate positions.…”
Section: Hierarchical Structurementioning
confidence: 96%
“…It does so by including the ethnicity and gender of employees jointly to obtain a more comprehensive measurement of workforce heterogeneity. In prior studies, the percent of Black, minority, or women officers in policing have served as dependent (or response) variables (e.g., Gustafson, 2013;Hochstedler & Conley, 1986;Kellough, 1990;Kim, 1993;Zhao, Herbst, & Lovrich, 2001). While these measures are useful for assessing ethnic or gender integration of specific populations into policing, they provide limited information in terms of the overall workforce diversity achieved by a police agency (e.g., Guajardo, 2015a).…”
Section: Recent Research On Ethnic and Gender Integration And Diversimentioning
confidence: 97%
See 2 more Smart Citations
“…As previously mentioned, past research on racial diversity in police departments has largely failed to integrate insights from minority threat theory (but see Gustafson 2013). The threat hypothesis predicts that minority and majority group members compete with each other for economic and political resources and higher levels of minority group representation increase potential competition between groups, creating a perception of threat among majority group members (Blalock 1967).…”
Section: Group Threatmentioning
confidence: 99%